New Evidence for the Existence of Two Kiss/Kissr Systems in a Flatfish Species, the Turbot (Scophthalmus maximus), and Stimulatory Effects on Gonadotropin Gene Expression - Zhao, Chunyan; Wang, Bin; Liu, Yifan; Feng, Chengcheng; Xu, Shihong; Wang, Wenqi; Liu, Qinghua; Li, Jun (Frontiers in Endocrinology, 2022)
Seasonal reproduction is generally controlled by the hypothalamus-pituitary-gonadal (HPG) axis in fish. Previous studies have demonstrated that the kisspeptin (Kiss)/kisspeptin receptor (Kissr) system, a positive regulator of the HPG axis, mediates the responses to environmental cues. Turbot (Scophthalmus maximus), a representative species of Pleuronectiformes, is one of the most commercially important fish species cultured in Europe and North China. However, the mechanisms by which the Kiss/Kissr system regulates the reproductive axis of turbot according to seasonal changes, especially photoperiod, have not been clearly characterized. In the current study, the cDNA sequences of kiss2/kissr2, along with kiss1/kissr3 which was thought to be lost in flatfish species, were cloned and functionally characterized. The kiss1, kiss2, and kissr3 transcripts were highly detected in the brain and gonad, while kissr2 mRNA was only abundantly expressed in the brain. Moreover, kiss/kissr mRNAs were further examined in various brain areas of both sexes. The kiss1, kissr2, kissr3 mRNAs were highly expressed in the mesencephalon, while a substantial degree of kiss2 transcripts were observed in the hypothalamus. During annual reproductive cycle, both kiss and kissr transcript levels declined significantly from the immature to mature stages and increased at the degeneration stage in the brains of both sexes, especially in the mesencephalon and hypothalamus. The ovarian kiss1, kiss2, and kissr2 mRNA levels were highest at the vitellogenic stage (mature stage), while expression of kissr3 was highest at the immature stage. The testicular kiss and kissr transcripts were highest in the immature and degeneration stages, and lowest at the mature stage. In addition, intraperitoneal injection of Kiss1-10 and Kiss2-10 significantly stimulated mRNA levels of pituitary lhβ, fhsβ, and gthα. In summary, two Kiss/Kissr systems were firstly proven in a flatfish species of turbot, and it has a positive involvement in controlling the reproduction of the Kiss/Kissr system in turbot. The results will provide preliminary information regarding how the Kiss/Kissr system controls seasonal reproduction in turbot broodstock.